Municipality Solid Waste Management. A Case Study of Smart City Bhubaneswar, Odisha - MOHANTY, Sasmita; MISHRA, Sitikantha; MOHANTY, Ashish (Journal of Environmental Management and Tourism, 2022)
Waste Management has become a big problem in India as a result of rapid urbanization. The urban population is around 377 million spread over 7,935 cities and towns who generates 62 million tones municipal solid waste per year. Only 43 million tons (MT) of the waste is collected, 11.9 MT is treated, and 31 MT is dumped in landfill sites. One of the essential services provided by Municipal Corporation is Solid Waste Management in order to keep the urban area clean. Further, The COVID-19 pandemic-induced catastrophe has altered the dynamics of waste generation in practically every sector around the world, necessitating specific attention. Unpredictable changes in trash quantity and composition also put pressure on policymakers to react quickly. Nevertheless, almost all the solid waste is dumped within the city haphazardly. It is believed that India had an unsound system of waste disposal management. This study was carried out to find out the issues if any regarding the solid waste management practices undertaken by Bhubaneswar Municipal Corporation and suggest certain remedial measures to improve the system.